Bending of Top Plates in Base Chair Connections - Dowswell, Bo (Engineering Journal, 2010)
In many heavy industrial facilities, column bases must transfer large uplift loads to the foundation, and if the tension load is too large to carry with a standard base plate, chairs are used to transfer the load. The top plate thickness has traditionally been determined using either the elastic one-way bending capacity of a beam spanning the distance between the vertical stiffener plates or the two-way bending capacity based on elasticity theory. These design methods can be used where the nominal stress must be limited to the elastic range, such as structures subject to fatigue. For static loads, a more realistic design model can be achieved by considering the plastic capacity of the plate in two-way bending. In this paper, the author develops a method to calculate the ultimate bending capacity of top plates in base chair connections based on yield line theory. The limit-analysis solution does not rely on the conservative assumptions inherent in calculation methods commonly used in design practice. The proposed equation can be used to calculate the capacity of many different base chair configurations, including those commonly used on plate and shell structures.